Developing English for Academic Purposes (EAP) teaching materials: a needs analysis of novice teachers (Revista Horizontes de Linguistica Aplicada, 2017)
AbstractThe Language without Borders (LwB) Programme is an educational policy which aims at promoting English learning at universities as well as promoting opportunities for teacher development. LwB teachers have to prepare their own English for Academic Purposes (EAP) teaching materials. Taking this into account, we seek to understand how the LwB Programme prepares these teachers to create EAP materials and  if they encounter any difficulties. A needs analysis was carried out through online surveys and semi-structured interviews. The former was sent to LwB teachers from all over Brazil, and the latter was conducted with teachers from one university. Based on the results we suggest some topics that could be addressed in the pedagogical meetings to address these teachers’ needs.Keywords: English for academic purposes, teacher training, Languages without Borders. O desenvolvimento de materiais didáticos de Inglês para Fins Acadêmicos (IFA): uma análise das necessidades de professores iniciantes ResumoO Programa Idiomas em Fronteiras (IsF) é uma política educacional que busca promover a aprendizagem de inglês na universidade e ser uma oportunidade de formação de professores, pois os professores-bolsistas do IsF devem preparar seu próprios materiais didáticos de Inglês para Fins Acadêmicos (IFA). Levando isso em consideração, buscamos entender como o Programa IsF prepara esses professores para elaborar materiais de IFA e se encontram dificuldades. Para tanto, foi conduzida uma análise de necessidades através de questionários online e entrevistas. Os questionários foram enviados para professores IsF de todo o Brasil e as entrevistas foram realizadas com professores de uma universidade. Com base nos resultados, sugerimos tópicos que podem ser trabalhados nas reuniões pedagógicas para responder Ã s necessidades dos professores.Palavras-chave: Inglês para fins acadêmicos; formação de professores; Idiomas sem Fronteiras.